The Factors Influencing Purchase Decisions in choosing Halal Cosmetic Products Bengkalis State Polytechnic Students (Case Study of Emina Cosmetic Products) - Imelda Wulandari; Tri Handayani (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study aims to determine the factors that influence the decision to purchase halal cosmetic products, especially Emina products among Bengkalis State Polytechnic students. This type of research is observational by distributing questionnaires to 100 respondents using the non-probability sampling method of selecting samples. The results of this study indicate that personal factors get a mean score of 4.08 classified in high class, social factors get a mean score of 4.08 classified as high class. So the most dominant factor influencing purchasing decisions for Emina products is Personal Factors, while the lowest factors influencing purchasing decisions for Emina products are Social Factors.In general, the characteristics of consumers in choosing halal cosmetic products have a good level of understanding. The need to use halal products is the biggest indicator in reflecting personal factors and social factors. In general, consumer awareness of the importance of consuming halal products (halal cosmetics) is quite good. Local halal cosmetics industry players should be able to create products with halal labeling, so as to improve product image and product quality.